SYNCHRONIZATION OF GnRH AND PGF2 ON THE REPRODUCTIVE PERFORMANCE IN ACEH CATTLE - Melia, Juli; Desita, Ella; Khalifah, Hadid; Justika, Wulan; Armansyah, Teuku; Hasan, Muhammad; Rosmaidar, Rosmaidar; Sayuti, Arman; Aliza, Dwinna; Wahyuni, Sri (Jurnal Kedokteran Hewan, 2024)
This study aims to determine the effect of administering gonadotropin-releasing hormone (GnRH) accompanied by prostaglandin F2 alpha (PGF2) on the reproductive performance of female Aceh cattle. In this study, eight female Aceh cattle were used, divided into two groups, group I (K1, n= 3) which received estrus synchronization treatment with PGF2 and group II (K2, n= 5) which received estrus synchronization treatment with PGF2 (25 mg/cow) and gonadotropin-releasing hormone (GnRH, 100 g/cow). GnRH injection in K2 was performed 48 hours after PGF2 injection. The estrus displays measured included onset, duration, and intensity of estrus. Blood collection for estrogen examination was taken from day 1 to day 5 after PGF2 injection, while progesterone examination was taken on days 7, 14, and 21 after artificial insemination. Ovarian response and pregnancy examinations were performed using transrectal ultrasonography (USG). Data on estrus appearance and steroid concentration were analyzed using the Mann-Whitney U test, and differences in pregnancy percentage were analyzed using the chi-square test. In contrast, the number of follicles, dominant follicle diameter, and corpus luteum were analyzed using a split-plot test. Oestrus intensity, oestrus onset, oestrus duration, pregnancy percentage, estrogen and progesterone concentrations, ovarian response in class II follicles, class III follicles, and CL size in K1 vs K2 showed no significant differences (P0.05). The effect of time on ovarian response in class III follicles and CL size showed a significant difference (P0.05). In contrast, the interaction between hormone administration and day of treatment on ovarian response in class II follicles, class III follicles, and CL size showed no significant difference (P0.05). Based on the research results, it was concluded that administration of GnRH accompanied by PGF2 tends to increase the reproductive performance of Aceh cattle.